2016
DOI: 10.1159/000444670
|View full text |Cite
|
Sign up to set email alerts
|

Relative Brain Size and Its Relation with the Associative Pallium in Birds

Abstract: Despite growing interest in the evolution of enlarged brains, the biological significance of brain size variation remains controversial. Much of the controversy is over the extent to which brain structures have evolved independently of each other (mosaic evolution) or in a coordinated way (concerted evolution). If larger brains have evolved by the increase of different brain regions in different species, it follows that comparisons of the whole brain might be biologically meaningless. Such an argument has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 58 publications
1
49
0
1
Order By: Relevance
“…Moreover, recent comparative evidence reveals that large brains in birds are a result of disproportionately enlarged pallial areas known to play key roles in avian cognition (Sayol et al. ). These studies suggest that whole brain size is indeed a useful tool of assessing general evolutionary patterns of brain and cognitive evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent comparative evidence reveals that large brains in birds are a result of disproportionately enlarged pallial areas known to play key roles in avian cognition (Sayol et al. ). These studies suggest that whole brain size is indeed a useful tool of assessing general evolutionary patterns of brain and cognitive evolution.…”
Section: Discussionmentioning
confidence: 99%
“…When more than one specimen per species was examined, we first estimated the average brain volume for each sex and then we estimated the species value as the mean brain volume of the two sexes. Despite the heterogeneous functional organization of the brain, the pallial areas associated with general-domain cognition represent a large fraction of the entire brain, are disproportionally larger in large brained birds and accurately predict variation in the whole brain when allometric effects are appropriately accounted for5960.…”
Section: Methodsmentioning
confidence: 99%
“…Following argumentation of Lendvai, Bókony, Angelier, Chastel, and Sol (), we have decided to use the size of the whole brain in our comparative analysis for two main reasons: (1) large availability of published data on whole‐brain volume/mass, and (2) tight correlations of whole‐brain volume with neuron density and volume of brain components, for example, associative pallium, responsible for domain‐general cognition abilities such as innovativeness and learning (Herculano‐Houzel, Collins, Wong, & Kaas, ; Sayol, Lefebvre, & Sol, ; Timmermans, Lefebvre, Boire, & Basu, ). Consistently, it has been shown that whole brain size positively correlates with several measures of behavioral flexibility and abilities to survive in novel ecological conditions (reviewed by Lefebvre & Sol, ).…”
Section: Methodsmentioning
confidence: 99%